Penerapan Prinsip Itikad Baik Dalam Perlindungan Hukum Bagi Merek Terkenal yang Tidak Terdaftar di Indonesia Berdasarkan Putusan Mahkamah Agung Nomor 600 K/PDT.SUS-HKI/2020 - Mutia Kirana Aprilia; R. Rahaditya (UNIVERSITAS PGRI YOGYAKARTA, 2023)
Abstract Brands contain the promise of producers to consistently provide certain characteristics, benefits, and services to consumers. Apart from being a symbol of identity, the brand has a price that motivates producers in various ways so that their brands can compete and become popular among the public. Imitation of a well-known mark that is not registered in Indonesia is an example of fraudulent conduct or bad faith in trademark registration. There are legal rules governing the protection of famous brands that are not registered in Indonesia so that the principle of good faith can be applied to avoid losses to brand rights holders and for consumer protection against the purchase of counterfeit branded goods. The case contained in the Supreme Court decision Number 600 K / Pdt.Sus-HKI / 2020 between NILOS GmbH &Co.KG against PT ASIA SANTOSO in the trademark dispute